Modelling of large wood export at a watershed scale. Issue 2 (22nd November 2021) - Komori, Daisuke; Sukegawa, Yuto; Chaithong, Thapthai; Kazama, So
Abstract: This study proposed a quantitative model for analysing the mass balance of large wood and its export on an annual scale at a watershed scale. The study sites are five dam reservoir watersheds of the Kitakami River catchment located in the north‐eastern part of Japan. From analyses on 20 years patterns of actual large wood export to target dam reservoirs, (1) the annual 24‐h maximum rainfall would be a key factor for the annual large wood recruitment, and (2) large wood export characteristics on an annual scale would be based on two relationships. Based on the earlier findings, the model consists of two frameworks: the rainfall‐induced analytical shallow landslide model for the large wood recruitment, and the double storage function with the lumped hydrological method at a watershed scale for the large wood entrainment. The model was used to re‐analyse 20 years of actual large wood export. The Nash–Sutcliffe values were 0.7 or more, which indicated satisfactory results with high reproductivity of simulation, for large wood export estimated using this model for four among five dam reservoir watersheds. Namely, our results could demonstrate that the landslide or slope failures are a significant procedure of large wood export, and the characteristics of large wood export can be defined by two relationships, which are the direct export of large wood caused by an increase in large wood recruitment with the extreme rainfall event, and the baseflow of large wood, which is mainly old large wood recruitment stored at the slopes and in the stream. Abstract : A quantitative model for analysing the mass balance of large wood (LW) and its export on an annual scale is developed. The model is consisted of the rainfall‐induced analytical shallow landslide model for LW recruitment and the two‐stage tank model for LW entrainment. The Nash–Sutcliffe values were 0.7 or more for LW export estimated using this model for four dam reservoir watersheds in the Tohoku region, Japan.